Effect of lime, blended fertilizer and vermicompost on maize (Zea mays) yield in Assosa district, north-western Ethiopia - ABEBE, ABDISA; YLI-HALLA, MARKKU; WOGI, LEMMA; BEKELE, ABDISSA (The Indian Journal of Agricultural Sciences, 2024)
Application of organic and mineral fertilizers improves crop productivity and availability of plant nutrients. Further investigation into their integral application is crucial to obtaining optimum crop productivity. A field experiment was conducted during 2020–21 and 2021–22 at experimental field station in Benshangul Gumuz, Assosa University, Assosa, Ethiopia to investigate the response of maize (Zea mays L.) yield to lime, blended NPSZnB fertilizer and vermicompost. Two lime levels, three vermicompost levels, and three blended fertilizer levels were factorially combined and laid out in a randomized complete block design (RCBD). The integral application of organic fertilizer with blended fertilizer with lime significantly affected the agronomic parameters. Grain yield, number of grains per cob, 1000-seed weights, plant height, and days to 50% tasseling were parameters most affected by the amendments. Integral application of 50% of the recommended rate of blended fertilizer and vermicompost with lime improved maize yield by 53%, while the application of NPSZnB and vermicompost individually improved maize yield by 34% and 22% over the control treatment. One tonne of vermicompost and lime could substitute 38 kg and 23 kg of blended fertilizer, respectively. In conclusion, the integrated application of NPSZnB and vermicompost with the recommended amount of lime was the best soil fertility management option. In terms of grain yield and net benefit, 4 t/ha lime, 2.5 t/ha vermicompost and 100 kg/ha blended fertilizers were recommended for optimum maize production in the Assosa area and similar agroecologies.